2020
DOI: 10.25105/jat.v7i1.6325
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Risiko Perusahaan, Intensitas Aset Tetap Dan Ukuran Perusahaan Terhadap Aggressive Tax Avoidance

Abstract: <p><em>This study aims to examine the effect of corporate risk taking, intensity of fixed asset and firm size on aggressive tax avoidance. This study uses secondary data from is manufacturing company during 2016-2018. Techniques and sampling used are using by purposive sampling. The data analysis technique used is multiple regression with the help of Statistical Package For Social Science (SPSS). The results of this study indicate that first, corporate risk taking has a significant positive effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
2
11
1
3
Order By: Relevance
“…Research conducted by Rizky & Puspitasari (2020) and Prihananto et al (2018) with corporate risk results positively affect Tax Avoidance. Based on the existing analysis, the hypothesis lodge is as follows: H2: Corporate risk has a positive influence on Tax Avoidance Leverage is the capability of a corporate to pay off all of its debts (both short and long-term).…”
Section: H1: Political Connection Has a Negative Influence On Tax Avo...mentioning
confidence: 94%
See 1 more Smart Citation
“…Research conducted by Rizky & Puspitasari (2020) and Prihananto et al (2018) with corporate risk results positively affect Tax Avoidance. Based on the existing analysis, the hypothesis lodge is as follows: H2: Corporate risk has a positive influence on Tax Avoidance Leverage is the capability of a corporate to pay off all of its debts (both short and long-term).…”
Section: H1: Political Connection Has a Negative Influence On Tax Avo...mentioning
confidence: 94%
“…(Romadona & Setiyorini, 2020). Based on research, (Prihananto et al 2018), Mulyati et al (2019), and Rizky & Puspitasari (2020) state that corporate risk has a positive influence on tax avoidance because, with a high level of risk, the level of tax avoidance in the company will also be higher. The rise and fall of corporate risk reflect the tendency of a company's leadership.…”
Section: Introductionmentioning
confidence: 99%
“…Ukuran perusahaan juga menjadi penentu tingkatan rasa percaya investor karena besarnya ukuran perusahaan, akan mempermudah perusahaan mendapatkan informasi yang akan meningkatkan nilai perusahaan. Perusahaan yang berukuran besar bisa menjadi daya tarik bagi investor demi penanaman modal sebab nilainya aktiva yang besar (Rizky & Windhy, 2020).…”
Section: Pengaruh Ukuran Perusahaan Terhadap Nilai Perusahaanunclassified
“…Fitria's (2018) research shows that corporate risk had a negative impact on tax avoidance. In contrast, Rizky and Puspitasari (2020) found that corporate risk had a positive impact on tax avoidance, but and Chasbiandani, Astuti, and Ambarwati (2019) conclude that corporate risk had no effect on tax avoidance.…”
Section: Introductionmentioning
confidence: 96%
“…H2: Capital intensity has a positive effect on tax avoidance. Company executives make management decisions (Rizky & Puspitasari, 2020). The executive can be categorized as either a risk-taker or risk-averse.…”
Section: Introductionmentioning
confidence: 99%